Respostas

2013-09-06T01:01:34-03:00
A) 7y+ 5-y+8=31
6y=31-8-5
6y=31-13 = 18
y=18/6 = 3

b) 5 (3-2a)=55
3.5 = 15
5.-2a = -10a
15 - 10a = 55
+15 - 55 = + 10a
-40= 10a
a = -40 / 10 = -4

c) 27=3.(x+3)
3.x = 3x
3.3 = 9
3x +9 = 27
3x=27-9 = 18
x = 18 / 3 = 6

d)16x+2 (7x+8)-9=67
16x + 14x + 16 - 9 = 67
30x +7 = 67
30x = 67 -7 = 60
x = 60/30 = 2

e) 10-2x=3x
10 = 3x + 2x = 5x
x = 10/5 = 2

f) x -3=6+ 4x
-3-6 = 4x - x
-9 = 3x
x= -9 / 3 = -3

g) 14x + 16= 18x - 24
16+24= 18x -14x
40 = 4x
x = 40 / 4 = 10

h) 16x-6-7x=1,5+2x
9x - 2x = 1,5 + 6
7x = 7,5
x= 7,5 / 7 = 1,07...

i) 6(4z+2)+7.(-5z+3)= 66
24z + 12 + -35z+21)=66
-11z = 66 - 12 - 21
-11z =66 - 33 = 33
-z=33/11 = 3 .(-1)
z= -3


Espero q tenha ajudado! !!
1 2 1